2018
DOI: 10.1093/cid/ciy016
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Polyfunctional Cytotoxic CD4+ T Cells in Mycobacterium avium Immune Reconstitution Inflammatory Syndrome in Human Immunodeficiency Virus-Infected Patients

Abstract: Advanced HIV infection was associated with impaired MAC responses. Restoration of monocyte responses and expansion of polyfunctional MAC-specific T-betlow CD4+ T cells with cytotoxic potential after ART initiation may overwhelm existing regulatory and inhibitory mechanisms, leading to MAC-IRIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
5
21
1
2
Order By: Relevance
“…Immune cells polyfunctionality, in terms of cytokine production, has been recently described in lymphocytes 44 and monocytes 10 , in the context of infectious diseases. In sterile inflammatory conditions such as SCA, the polyfunctionality still remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells polyfunctionality, in terms of cytokine production, has been recently described in lymphocytes 44 and monocytes 10 , in the context of infectious diseases. In sterile inflammatory conditions such as SCA, the polyfunctionality still remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility to disseminated mycobacterial infection is well described and should be considered in anyone who presents with disseminated disease without HIV infection (Wu and Holland, 2015). Even diseases that are often diagnosed in childhood can present with disseminated infection in adulthood when their mutation results in a less severe phenotype (Hsu et al, 2018). Host control depends on the interleukin 12-interferon pathway that connects myeloid and lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that using analysis of Spearman correlation matrices can provide insights on the degree and quality of inflammation in TB-HIV as well as in other diseases [26][27][28]. The results obtained from the canonical correlation model described above indicated that there were differences in the correlation profiles between the inflammatory markers from PTB vs. EPTB patients and we next utilized Circos plots to visualize such distinctions.…”
Section: Unique Correlation Profiles Of Inflammatory Biomarkers In Pementioning
confidence: 96%
“…Baseline and post treatment plasma samples originated from persons with signs and symptoms indicative of active TB and who were HIV-uninfected and who were not undertaking antitubercular therapy or healthy controls that were enrolled into a prospective clinical protocol to assess response to chemotherapy (NCT01071603) conducted at the Henan Chest Hospital (HCH) in Zhengzhou, China from 2010 to 2012, as described previously [6,15,16]. Individuals with pulmonary tuberculosis (PTB) were similar to those presenting with extra pulmonary tuberculosis (EPTB) with regard to age (median [IQR] in years: 27 [23-44.7] vs. 27 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], respectively; P = 0.1933; Supplemental Table 1) and gender (P = 0.4916, Table S1), with higher frequency of male individuals (61.7% vs. 52% vs. respectively).…”
Section: Characteristics Of the Study Participantsmentioning
confidence: 99%